1992
DOI: 10.1128/iai.60.3.944-950.1992
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor modulates endotoxin-induced macrophage procoagulant activity by a protein kinase C-dependent mechanism

Abstract: Macrophage procoagulant activity is an important mediator of extravascular fibrin deposition at sites of infection and appears to contribute to the pathogenesis of several infectious disease processes. Previous studies have shown that the inflammatory mediator platelet-activating factor was able to prime macrophages for induction of procoagulant activity by bacterial lipopolysaccharide. The present studies were designed to examine the mechanism of this priming effect. Platelet-activating factor (100 nM) primed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This agent completely prevented the release of PGE 2 by LPS-stimulated cells. Consistent with our previous reports (40), indomethacin had no effect on LPS-stimulated PCA (Fig. 8B).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This agent completely prevented the release of PGE 2 by LPS-stimulated cells. Consistent with our previous reports (40), indomethacin had no effect on LPS-stimulated PCA (Fig. 8B).…”
Section: Resultssupporting
confidence: 93%
“…Brozna and Carson (8) demonstrated that phorbol myristate acetate, at concentrations sufficient to translocate PKC activity from the cytosolic to the particulate fraction in adherent human monocytes, blocked adherence-induced PCA expression and suppressed PCA expression in cells activated by adherence or LPS treatment. Our laboratory has previously shown that PMA alone had little direct effect on PCA in thioglycolate-elicited murine peritoneal macrophages, although it primed cells for increased PCA expression in response to LPS and live bacteria (40,41). The variability observed with respect to the role of PKC in LPSinduced PCA in monocytes/macrophages may be related to the source of the cell studied as well as the degree of cellular activation.…”
Section: Figmentioning
confidence: 98%
See 1 more Smart Citation
“…As noted above, stimulated mast cells can release histamine, as well as neutral proteases and proteoglycans, TNF-␣ and other cytokines as preformed mediators, and arachidonic acid metabolites such as prostaglandin D 2 , leukotriene B 4 , and platelet activating factor as mediators synthesized de novo [49]. These mediators cause cellular and plasma protein influxes (including fibrinogen), and may have direct effects on resident and recruited cells relevant, e.g., to fibrin deposition (e.g., platelet-activating factor primes macrophages for LPS induction of PCA [50]). Mast cell lysates can induce macrophage PCA and TNF-␣ release [51].…”
Section: Mast Cells and Abscess Formationmentioning
confidence: 99%
“…Fibrin deposition is part of the pathological picture observed in each of these processes, suggesting that PAF contributes to the pathogenesis of these diseases by inducing local coagulation. In this regard, recent studies demonstrated the ability of PAF to augment the induction of procoagulant activity (PCA) in macrophages in response to LPS or tumor necrosis factor-a (Kucey et al, 1991a(Kucey et al, , 1992Maier et al, 1992). Moreover, several authors suggested that hypoxia, whose importance in the development of venous thrombosis has been acknowledged for a long time, induces the expression of PCA in cultured human umbilical vein endothelial cells (HUVEC) and mono-cytes Gertler et al, 1991;Kucey et al, 1991b).…”
mentioning
confidence: 99%